Plasma proteomic signature of age in healthy humans - Tanaka, Toshiko; Biancotto, Angelique; Moaddel, Ruin; Moore, Ann Zenobia; Gonzalez‐Freire, Marta; Aon, Miguel A.; Candia, Julián; Zhang, Pingbo; Cheung, Foo; Fantoni, Giovanna; Semba, Richard D.; Ferrucci, Luigi; et al. (Aging cell, 2018)
To characterize the proteomic signature of chronological age, 1,301 proteins were measured in plasma using the SOMAscan assay (SomaLogic, Boulder, CO, USA) in a population of 240 healthy men and women, 22–93 years old, who were disease‐ and treatment‐free and had no physical and cognitive impairment. Using a p ≤ 3.83 × 10−5 significance threshold, 197 proteins were positively associated, and 20 proteins were negatively associated with age. Growth differentiation factor 15 (GDF15) had the strongest, positive association with age (GDF15; 0.018 ± 0.001, p = 7.49 × 10−56). In our sample, GDF15 was not associated with other cardiovascular risk factors such as cholesterol or inflammatory markers. The functional pathways enriched in the 217 age‐associated proteins included blood coagulation, chemokine and inflammatory pathways, axon guidance, peptidase activity, and apoptosis. Using elastic net regression models, we created a proteomic signature of age based on relative concentrations of 76 proteins that highly correlated with chronological age (r = 0.94). The generalizability of our findings needs replication in an independent cohort.